Discovery of novel benzothiophene derivatives as potent and narrow spectrum inhibitors of DYRK1A and DYRK1B. (15th July 2022) - Segretti, Natanael D.; Takarada, Jéssica E.; Ferreira, Marcos A.; da Silva Santiago, André; Teodoro, Bruno V.M.; Damião, Mariana C.F.C.B.; Godoi, Paulo H.; Cunha, Micael R.; Fala, Angela M.; Ramos, Priscila Z.; Ishikawa, Eloisa E.; Mascarello, Alessandra; et al.
Graphical abstract: Abstract: The discovery of potent and selective inhibitors for understudied kinases can provide relevant pharmacological tools to illuminate their biological functions. DYRK1A and DYRK1B are protein kinases linked to chronic human diseases. Current DYRK1A/DYRK1B inhibitors also antagonize the function of related protein kinases, such as CDC2-like kinases (CLK1, CLK2, CLK4) and DYRK2. Here, we reveal narrow spectrum dual inhibitors of DYRK1A and DYRK1B based on a benzothiophene scaffold. Compound optimization exploited structural differences in the ATP-binding sites of the DYRK1 kinases and resulted in the discovery of 3n, a potent and cell-permeable DYRK1A/DYRK1B inhibitor. This compound has a different scaffold and a narrower off-target profile compared to current DYRK1A/DYRK1B inhibitors. We expect the benzothiophene derivatives described here to aid establishing DYRK1A/DYRK1B cellular functions and their role in human pathologies.